Penguatan Kelembagaan Wirausaha Wanita Tani pada Masyarakat Maritim di Kecamatan Moramo Kabupaten Konawe Selatan - Rahmah, Nur (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
The potential of coastal resources become a lifeline for households who live in the maritime area. However, the uncertain climate conditions cause seaweed production is not stable so the impact on household income uncertainty. Similarly, seaweed farming households in the village Ranooha which makes cultivation of seaweed as a source of household income. Seaweed production sometimes has a surplus so IbM activity is important to do. The involvement of all members of the family including housewives become one of the solutions to earn extra income to meet family needs. The involvement of all members of the family including housewives become one of the solutions to earn extra income to meet family needs. IbM activity aims to establish new entrepreneurship for women farmers to make processed seaweed in the form of prepared products (dodol and bajik of seaweed) to be marketed and is expected to be a source of additional income for the family. The method used is both physical and non-physical. Physical approach intended to solve the problems associated with production problems, by improving the production process, the infrastructure of production and processing of seaweed as raw material products, manufacturing of promotional media products as well as seeking product obtained a license from the relevant authorities, while the approach to non-physical related to problem-solving management is conducting socialization and training to women's groups and seek licensing and product licensing. The next activity was to build a network marketing and promotional activities of products. The results of the activities of IbM is the formation of product marketing network, has a product promotion media such as brochures or leaflets designed to promote attractive processed seaweed (dodol and bajik) with the appropriate packaging standard packaging for food products and to obtain a license from the health department district /city.